Impact of Raw Material Export Restrictions on Employment: Evidence from Panel Data - Dede Setiono (ETIKONOMI, 2023)
The extractive industry typically contributes limited direct employment in host countries, prompting some nations to consider export restrictions on raw materials to enhance domestic job opportunities. However, scholarly opinions on the efficacy of these policies vary widely. This study addresses this gap by utilizing an extensive dataset spanning over a decade and encompassing diverse countries. Employing a fixed-effect Ordinary Least Square (OLS) regression model with panel data from 74 countries from 2009 to 2021, this paper shows that raw material export restrictions do not affect employment rates. This fact challenges the prevailing notion that export restrictions inherently boost domestic employment. Consequently, a more comprehensive strategy, including economic diversification, technological investment, and alternative job creation measures alongside export controls, is essential to effectively address employment challenges within the extractive sector. JEL Classification: F1, J2, O1How to Cite:Setiono, D. (2023). Impact of Raw Material Export Restrictions on Employment: Evidence from Panel Data. Etikonomi, 22(2), 483 – 494. https://doi.org/10.15408/etk.v22i1.32172.